Macrophage phenotypic subtypes diametrically regulate epithelial-mesenchymal plasticity in breast cancer cells. Issue 1 (December 2016) - Yang, Min; Ma, Bo; Shao, Hanshuang; Clark, Amanda; Wells, Alan
Abstract Background Metastatic progression of breast cancer involves phenotypic plasticity of the carcinoma cells moving between epithelial and mesenchymal behaviors. During metastatic seeding and dormancy, even highly aggressive carcinoma cells take on an E-cadherin-positive epithelial phenotype that is absent from the emergent, lethal metastatic outgrowths. These phenotypes are linked to the metastatic microenvironment, though the specific cells and induction signals are still to be deciphered. Recent evidence suggests that macrophages impact tumor progression, and may alter the balance between cancer cell EMT and MErT in the metastatic microenvironment. Methods Here we explore the role of M1/M2 macrophages in epithelial-mesenchymal plasticity of breast cancer cells by coculturing epithelial and mesenchymal cells lines with macrophages. Results We found that after polarizing the THP-1 human monocyte cell line, the M1 and M2-types were stable and maintained when co-cultured with breast cancer cells. Surprisingly, M2 macrophages may conferred a growth advantage to the epithelial MCF-7 cells, with these cells being driven to a partial mesenchymal phenotypic as indicated by spindle morphology. Notably, E-cadherin protein expression is significantly decreased in MCF-7 cells co-cultured with M2 macrophages. M0 and M1 macrophages had no effect on the MCF-7 epithelial phenotype. However, the M1 macrophages impacted the highly aggressive mesenchymal-like MDA-MB-231 breast cancer cells to take on a quiescent, epithelial phenotype with re-expression of E-cadherin. The M2 macrophages if anything exacerbated the mesenchymal phenotype of the MDA-MB-231 cells. Conclusion Our findings demonstrate M2 macrophages might impart outgrowth and M1 macrophages may contribute to dormancy behaviors in metastatic breast cancer cells. Thus EMT and MErT are regulated by selected macrophage phenotype in the liver metastatic microenvironment. These results indicate macrophage could be a potential therapeutic target for limiting death due to malignant metastases in breast cancer.